2015
DOI: 10.21608/bvmj.2015.31803
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Clostridium perfringens isolated from some meat products by using PCR

Abstract: One hundred and twenty random samples of meat products from different supermarkets in El-Gharbia governorate including minced meat, beef burger, sausage, luncheon (30 samples of each) were collected. C. perfringenswas detected in meat products with an incidence 15%. The incidence of C.perfringens in minced meat, sausage, beefburger and luncheon was 16.67%, 23.33%, 16.67% and 3.33%, respectively. Typing of C.perfringens isolates revealed that the incidences of toxigenic and non-toxigenic strains were 83.33% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…Further biochemical tests were confirmative to C. perfringens; where isolates were positive for glucose, lactose and sucrose sugar fermentation; liquefied gelatin while they were negative for catalase and indole tests. The findings may be consistent with parallel studies carried out by Cowan et al (2004); ISO (2004); Abd Al-Tawab et al (2015).…”
Section: Discussionsupporting
confidence: 93%
“…Further biochemical tests were confirmative to C. perfringens; where isolates were positive for glucose, lactose and sucrose sugar fermentation; liquefied gelatin while they were negative for catalase and indole tests. The findings may be consistent with parallel studies carried out by Cowan et al (2004); ISO (2004); Abd Al-Tawab et al (2015).…”
Section: Discussionsupporting
confidence: 93%
“…According to multiplex PCR results as showing in table (2) and pic.1, out of examined C. perfringens isolates, 29.6% of isolates were confirmed as C. perfringens type A (cpa), and 3.7% isolate was C. perfringens type D (etx); while failed to detect enterotoxin production gene (cpe); which were in agree with (Erol et al, 2008) who reported that recent studies claimed that C. perfringens type A foodborne poisonings are rarely associated with enterotoxin encoding by the cpe gene it is only detected in (0-5%) of outbreaks isolates. So, our results are logically in agree with (Abd Al-Tawab et al, 2015) (Prabhu et al, 2013, (Salah El-din et al, 2015) who proved that all their PCR examined C. perfringens isolates gave a characteristic band at 402bp (cpa only); Torky and Hassan (2014) revealed 66% of multiplex PCR examined isolates gave bands at 402bp and 33.3% gave both bands at 402 and 541bp, which referring to C. perfringens type A (cpa) and C. perfringens type D (etx), respectively; while failed to detect either C. perfringens type B or C. While it disagreed with (Afshari et al, 2015) who detected type A (29.03%), type C (70.96%), and cpe (25.00%) toxin genes in examined C. perfringens isolates.…”
Section: Discussionsupporting
confidence: 89%